2017
DOI: 10.1371/journal.pone.0187343
|View full text |Cite
|
Sign up to set email alerts
|

Brain gray matter structural network in myotonic dystrophy type 1

Abstract: This study aimed to investigate abnormalities in structural covariance network constructed from gray matter volume in myotonic dystrophy type 1 (DM1) patients by using graph theoretical analysis for further clarification of the underlying mechanisms of central nervous system involvement. Twenty-eight DM1 patients (4 childhood onset, 10 juvenile onset, 14 adult onset), excluding three cases from 31 consecutive patients who underwent magnetic resonance imaging in a certain period, and 28 age- and sex- matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
(49 reference statements)
3
20
0
Order By: Relevance
“…Subcortical involvement in DM1 has repeatedly been ª 2020 The Authors. Annals of Clinical and Translational Neurology published by Wiley Periodicals LLC on behalf of American Neurological Association reported 26,28,29,[40][41][42] and this is confirmed in our study. Moreover only in the adult/late subgroup was the opposite result found, primarily located in the temporal lobe.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Subcortical involvement in DM1 has repeatedly been ª 2020 The Authors. Annals of Clinical and Translational Neurology published by Wiley Periodicals LLC on behalf of American Neurological Association reported 26,28,29,[40][41][42] and this is confirmed in our study. Moreover only in the adult/late subgroup was the opposite result found, primarily located in the temporal lobe.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding cross-sectional data, we confirmed that global GM atrophy occurs in DM1 patients, which has been well documented in other studies. [26][27][28][29] A detailed examination of the global volume results in each group yielded some interesting findings. In accord with normal expected aging, when inspecting the raw GM scores, the older HC group (HC-adult/late) showed a lower total volume score than the younger HC group (HC-pediatric).…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently published VBM studies in non-congenital DM1 patients largely confirmed a pattern of widespread cortical GM reduction affecting all lobes and frequently involving pre- and postcentral gyrus ( 14 , 33 , 38 , 40 , 41 , 43 , 44 , 56 , 58 ). Hippocampus atrophy was described by only few VBM studies ( 33 , 38 , 44 , 58 ) and in one study even correlated with episodic memory ( 33 ). Subcortical changes are also part of the pattern observed in non-congenital DM1 patients and involve striatum, thalamus and cerebellum, albeit to a variable extent in different studies.…”
Section: Introductionmentioning
confidence: 88%
“…In DM1, cognitive deficits were initially attributed to a low IQ or mental retardation, but recent studies show that this assumption was wrong for a large cohort of patients and mainly applies for cases of congenital myotonic dystrophy (CDM). In fact, for the classic phenotype of DM1, neuropsychological deficits are as variable as muscular symptoms, and even recent publications about the correlation of CTG-repeat size and neuropsychological deficits show contradictory study results ( 56 58 ). There seems to be a correlation between diffuse brain alterations in primarily white and secondary gray matter, linking the DM1 to the group of brain disconnection disorders ( 59 ).…”
Section: Extramuscular Symptomsmentioning
confidence: 99%